Behavior of Intramolecular π‐π Interactions with Doubly Degenerated Bond Paths Between Carbon Atoms in Opposite Benzene Rings of Diethenodihydronaphthalenes by QTAIM Approach. Issue 1 (9th January 2017) - Matsuiwa, Kohei; Sugibayashi, Yuji; Tsubomoto, Yutaka; Hayashi, Satoko; Nakanishi, Waro
Abstract: Dynamic and static nature of intramolecular π‐π interactions between ethylene moieties in diethenodihydronaphthanaphtalene (1 b ) and derivatives (2 b –12 b ) are elucidated by employing QTAIM‐DFA (QTAIM dual functional analysis). During the course of the investigations, doubly degenerated bond paths were detected between carbon atoms in opposite benzene rings of dibenzo‐derivative of1 b with an etheno‐bridge on the backside (11 b ). It must be very curious, since one BP should correspond to an interaction between two carbon atoms. Intramolecular π‐π interactions in1 b –12 b are all classified by the pure CS (closed shell) interactions. The interactions between ethylene groups, with no substituents as in1 b –8 b, are predicted to have the van der Waals (vdW) nature. Those for9 b –12 b have the hydrogen bond (HB) nature with no covalency, where the ethylene moieties are included in one or two benzene ring(s), except for10 b, if evaluated with MP2/6‐311G(3d). The character in10 b is close to the borderline area between the vdW and HB nature with no covalency, although should be the vdW type. The interactions in2 b –12 b evaluated with MP2/6‐311G(3d) are predicted to be somewhat stronger than the case with MP2/6‐311G(d), as a whole. Abstract : Doubly degenerated bond paths were detected between carbon atoms in the opposite phenyl groups of the dibenzo derivative of diethenodihydronaphthalene.